1998
DOI: 10.2169/internalmedicine.37.831
|View full text |Cite
|
Sign up to set email alerts
|

In-phase Chest Wall Vibration Decreases Dyspnea During Arm Elevation in Chronic Obstructive Pulmonary Disease Patients.

Abstract: In-phase chest wall vibration (IPV) is knownto decrease dyspnea in patients with chronic obstructive pulmonary disease (COPD) at rest and during leg exercise. In the present study, the effects of IPV (100 Hz) on dyspnea and arm fatigue during upper extremity activity were studied in 9 patients with COPD(mean FEV1? 0.95 /). Dyspnea and arm fatigue (modified Borg scale) and ventilatory variables were measured during arm elevation (AE) with weights lifted straight above the head with and without IPV. Mean dyspnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…A number of other strategies have been investigated for their potential role in the relief of breathlessness. Several small studies have shown that chest wall vibration reduces dyspnea in patients with COPD (272)(273)(274)(275). However, the timing and site of application of the vibratory stimulus are important variables, and to date there is no commercially available device for delivering chest wall vibration.…”
Section: Treatmentmentioning
confidence: 99%
“…A number of other strategies have been investigated for their potential role in the relief of breathlessness. Several small studies have shown that chest wall vibration reduces dyspnea in patients with COPD (272)(273)(274)(275). However, the timing and site of application of the vibratory stimulus are important variables, and to date there is no commercially available device for delivering chest wall vibration.…”
Section: Treatmentmentioning
confidence: 99%
“…Intriguingly, neural drive changes to the respiratory accessory muscles [48] have been implicated in the development of acute dyspnoea and COPD [49] , [50] . Indeed, vibration-induced augmentation of afferent feedback from the parasternal intercostal muscle spindles using vibration, reduces breathlessness in COPD [35] , [45] , [51] [53] , that may also, by lowering central neural drive for a given output force, represent improved respiratory mechanical efficiency [54] , [55] . However, the timing and site of application of a vibratory stimulus appear important but whose optimal characteristics and form of delivery are unknown [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Chest-wall vibration has been tested in patients with COPD [11,12] and progressive neurologic disorders [13]. There are practical limitations to consider as most of the studies for COPD were performed in a laboratory with therapists attaching vibrators to specific intercostal spaces with the goal of changing respiratory sensation.…”
Section: Physiologic Factorsmentioning
confidence: 99%